2021
DOI: 10.3390/vaccines9121469
|View full text |Cite
|
Sign up to set email alerts
|

Intention of Parents to Immunize Children against SARS-CoV-2 in Italy

Abstract: Several countries have targeted adolescents for immunization against SARS-CoV-2 to mitigate COVID-19 spread. In Italy, immunization for children ≥ 12 years has been available starting from June 2021. We conducted a cross-sectional study to investigate the knowledge, attitude and intention to vaccinate children < 18 years in Italian families. We used a multinomial logistic regression model to investigate factors associated with intention to vaccinate. We collected a total of 1696 responses. Among the 491 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 24 publications
7
29
2
3
Order By: Relevance
“…For example, a study showed that parents who are anxious from COVID-19 are keener to vaccinate children [ 31 ]. Another study showed that the perceived danger of being infected with COVID-19 is one of the determinants for parents’ willingness to vaccinate children [ 18 ]. Additionally, another research found that the readiness to get the COVID-19 vaccine increases with a higher perceived susceptibility to COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a study showed that parents who are anxious from COVID-19 are keener to vaccinate children [ 31 ]. Another study showed that the perceived danger of being infected with COVID-19 is one of the determinants for parents’ willingness to vaccinate children [ 18 ]. Additionally, another research found that the readiness to get the COVID-19 vaccine increases with a higher perceived susceptibility to COVID-19 [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arab countries also reported similar trends in COVID-19 hesitancy [ 15 17 ]. Certainly, individuals who are hesitant in getting vaccinated query the usefulness and safety of vaccines for their children [ 18 ]. In Italy, a cross-sectional study was conducted to evaluate the knowledge, attitude, and intention to vaccinate children < 18 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present sample included adolescents aged 12–17 years from a specific German region who decided to receive a vaccination against COVID-19. Although vaccination willingness is relatively high in Germany overall [ 30 ], recent international studies show that the decision to receive a COVID-19 vaccination in children and adolescents depends on vaccine safety and efficacy, the perceived risk of infection transmission, and specific socio-demographic variables [ 31 , 32 , 33 ]. The willingness to receive a vaccination is increased in older adolescents, in those using more social media, and those having both parents vaccinated [ 32 ]; the willingness is decreased in those with higher distress over the effects [ 31 ], and in families with a lower income and a migrant background [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although vaccination willingness is relatively high in Germany overall [ 30 ], recent international studies show that the decision to receive a COVID-19 vaccination in children and adolescents depends on vaccine safety and efficacy, the perceived risk of infection transmission, and specific socio-demographic variables [ 31 , 32 , 33 ]. The willingness to receive a vaccination is increased in older adolescents, in those using more social media, and those having both parents vaccinated [ 32 ]; the willingness is decreased in those with higher distress over the effects [ 31 ], and in families with a lower income and a migrant background [ 33 ]. This is in line with the results of the present sample, as parental education level was high (>80% had a high or medium level of education) [ 15 ] suggesting a higher socio-economic status (SES) of the participating families.…”
Section: Discussionmentioning
confidence: 99%